Introduction to philosophy - thinking and poetizing - Heidegger, Martin (Indiana University Press, 2017)
First published in 1990 as the second part of volume 50 of Heidegger's Complete Works, Introduction to Philosophy presents Heidegger's final lecture course given at the University of Freiburg in 1944 before he was drafted into the German army. While the lecture is incomplete, Heidegger provides a clear and provocative discussion of the relation between philosophy and poetry by analyzing Nietzsche's poetry. Here, Heidegger explores themes such as the home and homelessness, the age of technology, globalization, postmodernity, the philosophy of poetry and language, aesthetics, and the role of philosophy in society. Translated into English for the first time, this text will be of particular interest to those who study Heidegger's politics and political philosophy.